Protocol for a multisite study on the efficacy of transcranial direct current stimulation as an adjuvant to naming and spelling therapy in the treatment of oral and written naming in individuals with primary progressive aphasia - Masson-Trottier, Michèle; Tippett, Donna; Rapp, Brenda; Harvey, Denise Y.; Roncero, Carlos; Vnenchak, Leslie; Faria, Andreia; Frangakis, Constantine; Chertkow, Howard; Hamilton, Roy H.; Hillis, Argye E.; Tsapkini, Kyrana (Frontiers in Human Neuroscience, 2025)
Primary progressive aphasia (PPA) is a neurological syndrome characterized by the gradual deterioration of language capabilities. Due to its neurodegenerative nature, PPA is marked by a continuous decline, necessitating ongoing and adaptive therapeutic interventions. Recent studies have demonstrated that behavioral therapies, particularly when combined with neuromodulation techniques such as transcranial direct current stimulation (tDCS), can improve treatment outcomes, including the long-term maintenance and generalization of therapeutic effects. However, there has yet to be a phase II multisite study examining the efficacy of tDCS in individuals with PPA. This paper reports the methods and analyses for the clinical trial NCT05386394. A total of 120 adults with non-fluent and logopenic variant PPA will receive a novel spoken Naming and Spelling (NaSp), individuals with semantic variant PPA will be excluded from this trial. Participants will receive NASP therapy over two periods of 3 weeks (Monday through Friday, for a total of 15 non-consecutive days) combined with anodal (a-tDCS) and sham tDCS (s-tDCS). They will be randomly allocated to receive a-tDCS either during the first or second intervention period. The study will be conducted at four sites across the United States and Canada. Outcome measures will be recorded immediately before and after each intervention period, as well as 3 months after each period. Primary outcome measures will be the change in phonemic accuracy in spoken picture naming and letter accuracy in spelling for trained nouns and verbs. Changes from the a-tDCS and s-tDCS periods will be compared to determine the efficacy of tDCS. Primary outcomes will be analyzed using statistical methods that account for repeated measures within participants (namely generalized estimating equations). A significant adjuvant effect of tDCS will be determined if differences in phonemic accuracy and/or letter accuracy immediately following a-tDCS intervention and/or at the 3-month follow-up are greater (at p < 0.05) than those of the s-tDCS intervention. This trial is the first multisite, fully powered, randomized, double-blind, sham-controlled, crossover study of the effectiveness of tDCS as an adjuvant to behavioral treatment for spoken naming and spelling deficits in individuals with PPA. Specific challenges in designing the protocol are considered.